Examination of the exercise dependence scale-revised in asymptomatic individuals and individuals displaying pathogenic eating behaviors - Tracy, Erin Nicole, author; Rickard, Kathryn, advisor; Chen, Peter, committee member; Kennedy, Catherine, committee member; Ross, Stephen, committee member (Colorado State University. Libraries, 2010)
This investigation had two primary objectives. The first objective was to conduct both exploratory and confirmatory factor analyses on the Exercise Dependence Scale- Revised (EDS-R; Symons Downs, Hausenblas, and Nigg, 2004). These analyses provided information regarding the applicability of the seven DSM-IV Substance Dependence criteria to the assessment of exercise dependence. The second objective of the present investigation was to explore the relations between exercise dependence, as defined by factors that emerged from the factor analyses, and two related personality characteristics, addictiveness and obsessive-compulsiveness. Our earlier research examined the relations between exercise dependence and addictiveness and between exercise dependence and obsessive-compulsiveness in a sample who self-reported no symptoms of disordered eating (i.e., the asymptomatic sample). The present study examined the same relations in a sample who self-reported at least one pathogenic eating behavior (i.e., the symptomatic sample). Amount of exercise and weight dissatisfaction were also included in the correlational analyses. Results were discussed with regard to a model of the relations between addictiveness, obsessive-compulsiveness, exercise attitudes, and exercise behavior (Davis, Katzman, & Kirsh, 1999).
Covers not scanned.
Keywords: Exercise -- Psychological aspects; Eating disorders; Obsessive-compulsive disorder